STUDY OF MECHANISMS OF PUBLIC ADMINISTRATION IN HIGHER EDUCATIONAL INSTITUTIONS WITH SPECIFIC CONDITIONS OF EDUCATION - Meiko О.; Pavlov, S. (Honor and Law, 2020)
The problem of national security in Ukraine has become especially relevant. In this regard, first of all, the domestic science faces an extremely important and responsible task to develop a set of issues related to determining the foundations of national security, among which the first place is occupied by the training of qualified personnel. The purpose of the article is to analyze the theoretical foundations of the formation and development of mechanisms for public innovation management in higher education institutions with specific learning conditions. Based on our own practical experience and analysis, we add that in contrast to higher education institutions of the Ministry of Education and Science of Ukraine, in higher military educational institutions (institutions with specific training conditions) less attention is paid to the implementation of innovation. The National Agency for Quality Assurance in Higher Education (National Agency) also encourages the introduction of innovative activities in the educational process. In our opinion, the main value of the National Agency is innovation, namely the ability to produce and implement new, absent in domestic practice ideas, technologies, methods related to quality assurance in higher education. The state policy on introduction of innovations in management of higher educational institutions by these specific conditions of training should be realized by the corresponding mechanisms of public management which introduction is based on definition of the purpose of innovation policy, object of innovative changes learning conditions. Areas of further research will focus on the study of mechanisms of public innovation management in the management of higher education institutions with specific learning conditions.